If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 21 = 3x + -45 Reorder the terms: 21 + 6x = 3x + -45 Reorder the terms: 21 + 6x = -45 + 3x Solving 21 + 6x = -45 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 21 + 6x + -3x = -45 + 3x + -3x Combine like terms: 6x + -3x = 3x 21 + 3x = -45 + 3x + -3x Combine like terms: 3x + -3x = 0 21 + 3x = -45 + 0 21 + 3x = -45 Add '-21' to each side of the equation. 21 + -21 + 3x = -45 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = -45 + -21 3x = -45 + -21 Combine like terms: -45 + -21 = -66 3x = -66 Divide each side by '3'. x = -22 Simplifying x = -22
| 0-3(m-2)=8 | | 9-5t=3t-15 | | 4r^6-9r^6=0 | | 8(x-1.2)=2.4 | | y(n)=0.25y(n-2)+x(n) | | 4x+4=4x+2 | | 8x-47=-x-17 | | 0.7x+11.8=x-2.09 | | 7x^2-56-41x=0 | | 5.8+0.9x=0.4 | | cos^3(x)+cos(x)=0 | | 6n+13=-14 | | 0.8n+2.9n-4.4=3 | | Cos(x)+1=2sin^2(x) | | 3d+1=22 | | 36/28 | | -2.8=-0.1p | | 20=8+3(12+x) | | 0.25d-11.6=2.45d | | 3q-3=3(q-1) | | 11.3-p=4.2 | | 6+5x+5x=76 | | 4x+20x=180 | | 2(x+7)=8(x+4) | | 1.25(a-9)=13/4 | | 8b-7b=2+7 | | -5m+27-3(m-1)=8m-(6m-3)-7m+9 | | N/6=9/10 | | 440/(2 | | (D^2-4D+4)y=x^3 | | 600x-0.03=100x+0.57 | | 40+5p=2p |